CIVIL WAR LITERATURE IN THE USA IN LITERARY CRITICISM - Liudmyla V. Pasko (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The article analyzes the impact of the war between the North and the South on American literature and shows why this war was a different material for artistic representation than the American Revolution and the War for Independence. By the time there appeared the first Civil War novels, American literature had already accumulated sufficient experience in artistic interpretation of war in the works dedicated to the American Revolution and the War for Independence. The works by J.F. Cooper, J. Kennedy, H. Melville, and N. Hawthorn revealed a truly rebellious spirit of American romantics, which allowed interpreting the past in terms of the present. But in the 60s of the 19th century the critical mood of the romantic novels of the 30–50s of the 19th century turned into didactic declarations and apology of purely regional aspirations, while the psychological and philosophical novels of N. Hawthorn and H. Melville were consigned to oblivion. And though the political situation at the time of the American Revolution and the War Between the States seemed almost similar, the Civil War appeared to be quite a different material for artistic realization. A truly epic comprehension of its problems was opposed by a long lasting mutual hatred of representatives of both camps. The question about the Civil War influence on literature occurred as far back as the very beginning of war actions. In the article “War and Literature” (1862) John Weiss subjected the history of liberating wars in some countries to a thorough analysis and arrived at the conclusion that war can have either stimulating, or demoralizing pressure upon the intellectual life of the country. In his opinion, the literary situation in the USA didn’t encourage the appearance of a new “Iliad”. Such a pessimistic forecast was later supported in the article “The Spirit of American Literature” by J. Macy, who considered that even if there hadn’t been created a single Civil war novel, incapability of American literature to create a real masterpiece on the basis of that conflict would have been less depressing. This point of view was shared by many researches. And though in the best book reviews (e.g. W.D. Howells’ review of “Miss Ravenel’s Conversion from Secession to Loyalty” by J.W. De Forest, 1867), and monographs by F.L. Pattee (“A History of American Literature since 1870”, 1915) and C. Van Doren (“The American Novel”, 1921), the basic trends in war literature development were touched upon, it was not until 1930s that Civil War literature became the subject of a special investigation. The first American investigator who tried to oppose the prevailing opinion was R.W, Smith. In her dissertation “The Civil War and Its Aftermath in American Fiction, 1861–1899” (1932) published in 1937, she insisted on the necessity of a thorough investigation of war literature within the context of the time that gave birth to it. But that was only the beginning of numerous discussions in literary criticism which this article comments on. R